Distribution of mitochondrial nucleoids upon mitochondrial network fragmentation and network reintegration in HEPG2 cells - Tauber, Jan; Dlasková, Andrea; Šantorová, Jitka; Smolková, Katarína; Alán, Lukáš; Špaček, Tomáš; Plecitá-Hlavatá, Lydie; Jabůrek, Martin; Ježek, Petr (The international journal of biochemistry & cell biology, 2013)
Mitochondrial DNA (mtDNA) is organized in nucleoids in complex with accessory proteins, proteins of mtDNA replication and gene expression machinery. A robust mtDNA genome is represented by hundreds to thousands of nucleoids in cell mitochondrion. Detailed information is lacking about the dynamics of nucleoid distribution within the mitochondrial network upon physiological and pathological events. Therefore, we used confocal microscopy to study mitochondrial nucleoid redistribution upon mitochondrial fission and following reintegration of the mitochondrial network. Fission was induced by oxidative stress at respiration inhibition by rotenone or upon elimination of the protonmotive force by uncoupling or upon canceling its electrical component, ΔΨ(m), by valinomycin; and by silencing of mitofusin MFN2. Agent withdrawal resulted in concomitant mitochondrial network reintegration. We found two major principal morphological states: (i) a tubular state of the mitochondrial network with equidistant nucleoid spacing, 1.10±0.2 nucleoids per μm, and (ii) a fragmented state of solitary spheroid objects in which several nucleoids were clustered. We rarely observed singular mitochondrial fragments with a single nucleoid inside and very seldom we observed empty fragments. Reintegration of fragments into the mitochondrial network re-established the tubular state with equidistant nucleoid spacing. The two major morphological states coexisted at intermediate stages. These observations suggest that both mitochondrial network fission and reconnection of the disintegrated network are nucleoid-centric, i.e., fission and new mitochondrial tubule formation are initiated around nucleoids. Analyses of combinations of these morphological icons thus provide a basis for a future mitochondrial morphology diagnostics.
Keywords: replikace DNA; mitochondriální dynamika; Mitochondrial Proteins; Mitochondria; Microscopy, Confocal; DNA vazebné proteiny; DNA-Binding Proteins; buňky Hep G2; konfokální mikroskopie; Humans; mitochondrie; DNA, Mitochondrial; Hep G2 Cells; mitochondriální DNA; Mitochondrial Dynamics; mitochondriální proteiny; lidé; DNA Replication